Label-free Evaluation of Carbon Nanoparticles in Layer-by-Layer Self-assembled Enzyme-based Biosensors. (2017) - David, Melinda; Florescu, Monica; Barsan, Madalina M.; Brett, Christopher M.A.
Abstract: The immobilization of biomolecules and the enhancement of the electron transfer are important factors regarding the performances of the enzyme-based biosensors. Layer-by-layer (LbL) strategies can be effectively used to reduce diffusion time of analytes and improve analyte access to the reaction sites, as well as minimizing biomolecule denaturation. In this work, glucose oxidase (GOx) was incorporated in a multilayer film on a gold electrode. Prior the LbL formation, the Au surface was modified with a film of conducting polymer poly(3, 4-ethylenedioxythiophene) (PEDOT), by electropolymerization. Multilayer films containing the enzyme and nitrogen doped graphene (NG) dispersed in the biocompatible positively-charged polymer chitosan {chit + (NG+GOx)}, together with the negatively charged poly(styrene sulfonate), PSS -, were assembled and evaluated using different methods. The biosensor response toward glucose was linear in the range of 0.2 - 1.5 mM, with a sensitivity of 128 ± 4 μA cm -2 mM -1 and a detection limit of 94.3 ± 8.9 μM. The biosensor maintained its stability for two weeks. The {chit + (NG+GOx)/PSS − } bilayer-based biosensor was used successfully for glucose detection in plant extracts.